OC-057 10 Years on from the improving outcomes guidance—development of a tertiary pancreatic cancer unit. (28th May 2012) - Johnstone, M; Halloran, C M; Ghaneh, P; Sutton, R; Neoptolemos, J P; Raraty, M G T
Abstract : Introduction: In 2001 the National Institute for Clinical Excellence (NICE) published guidance on best practice for cancer services entitled Improving Outcomes Guidance (IOG). These guidelines specified centralisation, increased patient volume (>200 referrals/year), improved resection rates (>10%–15%) and reduced post-operative mortality rates (<5%). We looked at the development of a regional tertiary pancreatic centre over the 10 years following this, and how practice has changed over this time. Methods: A prospectively maintained database of all referrals with suspected pancreatic cancer to the Supra-Regional Pancreas Centre in Liverpool was interrogated to assess changes in practice and outcome from 2001 to 2010 inclusive. Data were analysed with χ 2 for trend for categorical data and log rank for survival data. Results: 2076 patients with malignancy were referred, rising from 73 in 2001 to 364 in 2010. 511 resections for malignancy were performed (25%), ranging between 21% (42/182) in 2005 and 36% (33/87) in 2003 per year, with no trend over time. 710 patients underwent planned operation for malignancy over the 10-year period ranging from 41 procedures in 2001 and peaking at 97 in 2008, with 94 procedures in 2009 and 88 cases in 2010. The percentage of planned resections that had a successful resection increased from 51% (21/41) in 2001 to 90% (79/88) by 2010 (p<0.001). The mortality from resection was 9/567 (2%) and overall was 5% (37/710) including palliative procedures. The 1 year survival rates of patients who underwent a successful resection improved from 65% (13/20) in 2001 to 76% (69/91) by 2009 (p=0.02). There has been a rise in the number of intraductal papillary mucinous neoplasm (IPMN) resected with none in 2001 increasing to 12 resections during 2009, 10 in 2010 and 212 patients currently undergoing surveillance for IPMN. The number of staging laparoscopies has remained fairly constant at around 27 per year, despite the increase in referrals, which reflects more stringent criteria in selecting these patients for laparoscopy. Conclusion: Over the last 10 years we have seen centralisation of services, which was completed in 2007. This has led to an increase in volume of cancer referrals in line with IOG guidance. Although resection rates have stayed constant, this reflects the increasing number of patients referred with irresectable disease for other treatments, including chemotherapy and novel cancer trials. There has been an improvement in case selection as demonstrated by a reduction in the percentage of bypass procedures, reflecting better pre-operative staging of patients. This has also lead to an improved 1-year survival in those patients who had a successful resection. Competing interests: None declared.